A Low Latency, Energy Efficient MAC Protocol for Wireless Sensor Networks. (25th August 2015) - Li, Zhe-tao; Chen, Qian; Zhu, Geng-ming; Choi, Young-june; Sekiya, Hiroo
Reducing unnecessary and redundant handshake frame is considered as a promising way to reduce the end-to-end delay and energy consumption. Here, a protocol named compressed handshake media access control (CH-MAC) is presented. CH-MAC introduces a new handshake mechanism with implicit RTS to achieve the object of low delivery latency and an initiative sleeping mechanism to settle the hidden terminal problem. Simulation results show that the proposed protocol outperforms SMAC protocol in both energy consumption and packet latency.